2018
DOI: 10.5935/1518-0557.20180027
|View full text |Cite
|
Sign up to set email alerts
|

Physiological ICSI (PICSI) vs. conventional ICSI in couples with male factor: A systematic review

Abstract: ObjectivesTo determine the efficacy of the physiological ICSI technique (PICSI) vs. conventional ICSI in the prognosis of couples with male factor, with respect to the following outcome measures: live births, clinical pregnancy, implantation, embryo quality, fertilization and miscarriage rates.MethodsA systematic review of the literature, extracting raw data and performing data analysis. Patient(s): Couples with the male factor, who were subjected to in-vitro fertilization. Main Outcome Measures: rates of live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
2
16
0
1
Order By: Relevance
“…Reviews and meta-analyses considering the efficacy of hyaluronan-based sperm selection for ICSI have been equivocal 5, 18, 19. Based on our study design, we can say with confidence that PICSI is not superior to standard ICSI for improving term livebirth rates, despite the reduction in miscarriage.…”
Section: Discussionmentioning
confidence: 78%
“…Reviews and meta-analyses considering the efficacy of hyaluronan-based sperm selection for ICSI have been equivocal 5, 18, 19. Based on our study design, we can say with confidence that PICSI is not superior to standard ICSI for improving term livebirth rates, despite the reduction in miscarriage.…”
Section: Discussionmentioning
confidence: 78%
“…These methods mostly include techniques such as intracytoplasmic morphologically selected sperm injection (IMSI), magnetic‐activated cell sorting (MACS) and physiologic intracytoplasmic sperm injection (PICSI). Although some promising preliminary results have been published regarding the use of these techniques (Dirican et al, ; Kim et al, ; Worrilow et al, ), recent reviews of the relevant clinical studies were insufficient to support their benefits in terms of clinical outcomes following IVF/ICSI (Avalos‐Duran et al, ; Stimpfel, Verdenik, Zorn, & Virant‐Klun, ; Teixeira et al, ). Also, the results of a recent preclinical study reported improved ICSI outcomes through sperm selection by thermotaxis in mice (Perez‐Cerezales et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…IMSI and PICSI are advanced ICSI-related techniques that are poorly studied (Avalos-Duran et al, 2018;Teixeira et al, 2020), as reflected in our scientometric results. IMSI is characterised by sperm selection based on morphological criteria under a high-resolution microscope (Kim et al, 2014;Oseguera-Lopez et al, 2019), whereas in PICSI, spermatozoa are selected using hyaluronic acid binding to mature and morphologically intact spermatozoa (Avalos-Duran et al, 2018).…”
Section: Despite Its Advantages Macs Is Yet To Be Certified By the Fmentioning
confidence: 79%
“…IMSI and PICSI are advanced ICSI-related techniques that are poorly studied (Avalos-Duran et al, 2018;Teixeira et al, 2020), as reflected in our scientometric results. IMSI is characterised by sperm selection based on morphological criteria under a high-resolution microscope (Kim et al, 2014;Oseguera-Lopez et al, 2019), whereas in PICSI, spermatozoa are selected using hyaluronic acid binding to mature and morphologically intact spermatozoa (Avalos-Duran et al, 2018). PICSI and IMSI have not shown many benefits in reproductive outcomes over conventional ICSI, including fertilization, implantation, clinical pregnancy, miscarriages and live birth rates, as well as embryo quality (Avalos-Duran et al, 2018;Teixeira et al, 2020).…”
Section: Despite Its Advantages Macs Is Yet To Be Certified By the Fmentioning
confidence: 79%
See 1 more Smart Citation